Roald Dahl and philosophy a little nonsense now and then - Held, Jacob M. 1977- (Rowman & Littlefield, 2014)
Classics like Charlie and the Chocolate Factory, James and the Giant Peach, Fantastic Mr. Fox, Matilda, and The BFG may initially appear to be yarns spun for the amusement of the adolescent mind. However, upon digging deeper, one uncovers a treasure trove of philosophical richness that is anything but childish, and which reveals the true existential weight, and multi-layered meaning of some of our favorite children's stories.